Visual "literacy" : image, mind, and reality - Messaris, Paul. (Boulder : Westview Press, 1994)
Four aspects of visual literacy. Still images ; Film and television ; Cognitive consequences of visual literacy ; Awareness of artistry and visual manipulation --##The interpretation of still images. Abstract representation ; Concrete representation ; Empirical evidence --##The interpretation of film and television. Point-of-view editing ; Editing as an indicator of thoughts and emotions ; The modulation of emphasis and viewer involvement ; Beyond point-of-view editing ; Propositional editing --##General cognitive consequences of visual literacy. Propositionality revisited ; Representational categories and world views ; Spatial intelligence ; From concrete to abstract to analogy --##Awareness of artistry and manipulation --##The detection of artifice ; Unconcealed artifice ; Visual manipulation --##Conclusion: Other questions, other "literacies". Images and the appearance of reality ; Images and cultures ; Familiarity with visual subject matter ; Production literacy".
Includes bibliographical references (p. 185-199) and index.
boek